Schumpeterian Entry: Innovation, Exporting, and Growth Aspirations of Entrepreneurs - Estrin, Saul; Korosteleva, Julia; Mickiewicz, Tomasz (Entrepreneurship Theory and Practice, 2022)
We posit that entrepreneurs who engage in strategic activities will have high growth aspirations. Our proposed mechanism is that strategic engagements, specifically product innovation, process innovation and internationalization, open entrepreneurial ventures to learning, and thereby greater growth opportunities. Furthermore, these learning effects are reinforced in research-intensive industrial environments. We apply multilevel random slope estimation for individuals from 74 countries, 2001–2015, to derive results consistent with our hypotheses. The findings are robust to potential reverse causality between strategic behavior and growth aspirations, and to selection bias resulting from strategic engagements being only observed for actual entrepreneurs.